Nasze małe umieranie. Doświadczenie przemijalności świata w kontekście życia potocznego - Wieczorek, Krzysztof T. (Folia Philosophica, 2018)
The paper offers a tentative analysis of some possible forms of the experience of world fading and impermanence of one’s existence as contemporary agent, immersed in world of everyday life. The starting point of the analysis is Jan Patočka’s model of “the natural man”. The author of the paper modifies it to make is suitable for description of civilization of the 21st-century human whose “natural world” is much more dense, more saturated with both technological artefacts and information, which he or she is able to assimilate only partially. The author claims that a man living in the environment suffused with items and information, spontaneously generates a strategy of evading important problems of life, and if it fails, found themself hopeless and lost. In some cases this feelings are generated by unexpected confrontation of their self-consciousness with the experience of inevitable fading, when — as Patočka rightly observes — the agent faces “spiritual shock”. The author outlines some of the consequences of this shock in the last part of the paper.